2022
DOI: 10.1002/eat.23770
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder behaviors as predictors of suicidal ideation among people with an eating disorder

Abstract: Objective: Suicidality is known to be elevated among people with an eating disorder.The aim of the current study was to examine whether any of three specific behavioral facets of eating disorders (i.e., purging, binge eating, restricting) would be the strongest predictors of suicidal ideation, controlling for one another, in longitudinal analyses from admission to discharge. We hypothesized that purging, above and beyond restricting or binge eating, would be the most important predictor of suicidal ideation.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…1It is important to acknowledge that participants who complete admission and discharge assessments may not be representative of those with only admission data. Past analyses on a related sample indicated attrition had no influence on outcomes (Joiner et al, 2022), and analyses on this sample further affirmed that view.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…1It is important to acknowledge that participants who complete admission and discharge assessments may not be representative of those with only admission data. Past analyses on a related sample indicated attrition had no influence on outcomes (Joiner et al, 2022), and analyses on this sample further affirmed that view.…”
mentioning
confidence: 66%
“…This single item was used as a proxy for Gaudiani et al’s (2022) fourth criterion for T-AN. The PHQ-9 is a well-validated measure (Kroenke & Spitzer, 2002; Kroenke et al, 2001; Spitzer et al, 2014), and regarding the one-item index of death ideation, there is evidence that such measures are defensibly reliable and valid (e.g., Joiner et al, 2022; Robison et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, we also tracked patients who selected “no days” (0 points). This item has been shown to be predictive of the risk of repeat suicide attempts and of suicide death (Green et al., 2015; Joiner et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, gender and sexual minorities are demonstrated to be particularly at risk for developing EDs, with anorexia nervosa and bulimia being the most prevalent [2][3][4]. Notably, compared to any other psychiatric conditions, anorexia nervosa and bulimia have the highest suicidality and mortality rates and lowest quality of life levels, highlighting the importance of urgency of care [5][6]. Research demonstrated that merely one-fourth of individuals with ED symptoms or developed EDs access care, which is explained by the lack of access to treatment and the individual's preference for treatment [7].…”
Section: Introductionmentioning
confidence: 99%